THE CONNECTION BETWEEN CULTURE AND FOOD TABOOS AMONG BREASTFEEDING MOTHERS: A LITERATURE REVIEW - Maria Fridolina Manehat; Ani Margawati; Nuryanto Nuryanto (Journal of Nutrition College, 2026)
ABSTRACTBackground: Optimal maternal nutrition during breastfeeding is crucial for the health of both mother and infant, yet many women face culturally rooted food taboos that restrict nutrient-rich foods, leading to reduced dietary diversity and micronutrient deficiencies. Culturally rooted food taboos, reinforced by food insecurity and limited nutrition education, highlight the need for context-sensitive strategies to improve maternal and infant health. Objectives: This literature review explores the nutritional consequences of cultural food taboos among breastfeeding mothers and their implications for maternal and infant health.Methods: This study employed a literature review approach,  to identify and synthesize existing research on food taboos among breastfeeding mothers. A systematic search was conducted in the PubMed database using the keywords “food taboo”, “culture”, and “breastfeeding mothers”. After applying inclusion and exclusion criteria, four relevant articles published between 2015 and 2025 were selected. Data were extracted and thematically analyzed to explore cultural rationales and nutritional implications.Results Food taboos during breastfeeding often limit nutritious foods and may lead to nutrient deficiencies in mothers and infants. These taboos are shaped by culture and beliefs, and understanding their social meaning is key. Respectful, culturally sensitive nutrition education can help improve health outcomes.Conclusion: Food taboos among breastfeeding mothers, though intended to protect health, can reduce dietary diversity and lead to micronutrient deficiencies, affecting maternal recovery, breast milk quality, and infant development. Effective interventions should be culturally sensitive and grounded in an understanding of the sociocultural meanings behind these practices.Keywords: Breastfedding mothers; culture; food taboos ABSTRAKLatar belakang: Gizi yang optimal pada ibu menyusui sangat penting untuk kesehatan ibu maupun bayi, namun banyak perempuan menghadapi pantangan makanan yang berakar pada budaya, yang membatasi konsumsi makanan bergizi dan menyebabkan rendahnya keberagaman makanan serta kekurangan mikronutrien. Pantangan makanan yang dilandasi budaya, diperkuat oleh ketidakamanan pangan dan minimnya edukasi gizi, menekankan perlunya strategi yang sensitif terhadap konteks untuk meningkatkan kesehatan ibu dan anak.Tujuan: Tinjauan pustaka ini membahas dampak nutrisi dari pantangan makanan berbasis budaya pada ibu menyusui serta implikasinya terhadap kesehatan ibu dan bayi.Metode: Penelitian ini menggunakan pendekatan tinjauan pustaka untuk mengidentifikasi dan mensintesis penelitian yang telah ada mengenai pantangan makanan pada ibu menyusui. Pencarian sistematis dilakukan melalui basis data PubMed dengan menggunakan kata kunci “food taboo”, “culture”, dan “breastfeeding mothers”. Setelah menerapkan kriteria inklusi dan eksklusi, empat artikel relevan yang diterbitkan antara tahun 2015 hingga 2025 dipilih. Data dari artikel tersebut diekstraksi dan dianalisis secara tematik untuk menggali alasan budaya dan implikasi nutrisinya. Hasil: Pantangan makanan selama menyusui seringkali membatasi konsumsi makanan bergizi dan dapat menyebabkan kekurangan nutrisi pada ibu dan bayi. Pantangan ini dibentuk oleh budaya dan kepercayaan, dan memahami makna sosialnya sangat penting. Pendidikan gizi yang menghormati dan peka terhadap budaya dapat membantu meningkatkan hasil kesehatan.Simpulan: Pantangan makanan pada ibu menyusui, meskipun bertujuan melindungi kesehatan ibu dan bayi, dapat mengurangi keberagaman makanan dan menyebabkan defisiensi zat gizi mikro, sehingga berdampak pada pemulihan ibu, kualitas ASI, dan tumbuh kembang bayi. Pendekatan intervensi yang efektif perlu mempertimbangkan makna sosial budaya dari praktik ini melalui pemahaman yang sensitif dan menghargai budaya.Kata Kunci: Budaya; ibu menyusui; pantang makanan